استخدام فيلم الكرتون لتنمية مهارة الاستماع - Mustapa Mustapa (Lugawiyyat, 2020)
Many teachers do not care about the importance of educational means in the teaching and learning process. Some use them disproportionately to the conditions of a student and the subject, and some have not trained in it and do not believe in its usefulness and usefulness. The problem are (1) how is using of the cartoon film in teaching listening skill to second class at senior Islamic High School Nahdatul Ulama Gondang Legi Malang and (2) how far the effectiveness of using of the cartoon film in teaching listening skill to second class at senior Islamic High School Nahdatul Ulama Gondang Legi Malang. This research is experiment research. The sources data are teachers and students. The data collection methods used are interviews, observation and test.And the results of this research is the using of cartoon film before the average pre-test groups for the experiment is 67,38. While the using of cartoon film the average value achieved in the post test groups for the experiment is 85,24. And this results shows that the using of cartoon film in the teaching listening skill is very effective. The average pre test- for the control group is 40, and 90 post-test was 44, 38. That result shows the using classical method in teaching listening skill is not very effective.